Collembola at three alpine subarctic sites resistant to twenty years of experimental warming - Alatalo, Juha M; Jägerbrand, Annika K; Čuchta, Peter (Scientific reports, 2015)
This study examined the effects of micro-scale, site and 19 and 21 years of experimental warming on Collembola in three contrasting alpine subarctic plant communities (poor heath, rich meadow, wet meadow). Unexpectedly, experimental long-term warming had no significant effect on species richness, effective number of species, total abundance or abundance of any Collembola species. There were micro-scale effects on species richness, total abundance, and abundance of 10 of 35 species identified. Site had significant effect on effective number of species, and abundance of six species, with abundance patterns differing between sites. Site and long-term warming gave non-significant trends in species richness. The highest species richness was observed in poor heath, but mean species richness tended to be highest in rich meadow and lowest in wet meadow. Warming showed a tendency for a negative impact on species richness. This long-term warming experiment across three contrasting sites revealed that Collembola is capable of high resistance to climate change. We demonstrated that micro-scale and site effects are the main controlling factors for Collembola abundance in high alpine subarctic environments. Thus local heterogeneity is likely important for soil fauna composition and may play a crucial role in buffering Collembola against future climate change.
Keywords: Biodiversity; Sweden; rostliny; Plants; klimatické změny; ekosystém; Arthropods; biodiverzita; Climate Change; Animals; členovci; Arctic Regions; Ecosystem; zvířata; Arktida; Švédsko